If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2w + -9 = -17 Reorder the terms: -9 + 2w = -17 Solving -9 + 2w = -17 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 2w = -17 + 9 Combine like terms: -9 + 9 = 0 0 + 2w = -17 + 9 2w = -17 + 9 Combine like terms: -17 + 9 = -8 2w = -8 Divide each side by '2'. w = -4 Simplifying w = -4
| 5w^2+30w+6=0 | | 16x(7-x)=160 | | 8x-2=28x+13 | | 9*(3x)+4*(3x)=30x+5 | | (4x+34)=(7x+10) | | 9y+5y+20=62 | | 3x-10x+16=9-12x-28 | | 6(x-1)=3(x+1) | | 5xy(x+y)= | | (y-2)(y+4)=0 | | 6=2(7-c) | | y=16-6 | | 8-23x-14=9x-30x-6 | | 25-1.25x=16-.5x | | 15x-20=14x-21 | | 7+x(4)=16 | | -5n-8=16m | | 4x-5-6=12x-x-4-3x-7 | | 10n=9n+27 | | 24-8x=-2x+-10 | | x-(3x+7)=29 | | d-1=-9 | | 4x+(-4x)-2y+2y=-10+(-12) | | x+26-8x=8-4x | | 3x-6=60 | | q-e-(-2)=7-q | | 36=39 | | x^3-4x^2-11x+2=0 | | (2x+56)=(8x+8) | | 6x-18=30-2x | | w^2+6w+14=0 | | 2(x+8)=2x+16 |